Combustion and emission performance of a split injection diesel engine in a double swirl combustion system. (1st November 2016) - Li, Xiangrong; Gao, Haobu; Zhao, Luming; Zhang, Zheng; He, Xu; Liu, Fushui
Abstract: The authors developed and tested a split injection strategy in a double swirl combustion system (DSCS). Different split injection strategies with different ratios of pilot injection fuel to total fuel mass (herein defined as "pilot injection/fuel mass ratios") and dwell times were compared with an optimized single injection strategy in terms of the break specific fuel consumption (BSFC). The in-cylinder pressure, heat release rate and in-cylinder temperature were analyzed to explore the in-cylinder combustion process. The NOx emission was also measured. With the total fuel mass being 100 mg/cycle and excess air coefficient being 2 at 2100 r/min at a 5% pilot injection/fuel mass ratio and a 10 deg dwell time, the BSFC decreased by 2.7% compared with the single injection strategy. The NOx emission increased from 940 ppm to 1140 ppm. An 'acceleration effect' helped the DSCS when dwell time was short. A spray visualization experiment and numerical simulations were carried out to explain these phenomena. It is concluded that the split injection condition with a smaller pilot injection/fuel mass ratio and a shorter dwell time performed better than the single injection condition in terms of the thermo-atmosphere utilization, space utilization and acceleration effect. Highlights: Split injection strategies are applied in a double swirl combustion system (DSCS). The combustion performance of split injection strategies in the DSCS is analyzed. The NOx emissions of split injection strategies in the DSCS are monitored. The mechanism is discussed by a visualization experiment and numerical simulations.